A comparison of parent and professional perceptions of children with autism spectrum disorder in Portugal - Reis, Helena Isabel da Silva (2017)
Improving early intervention in Portugal for children with autism spectrum disorder (ASD) requires parents and professionals to collaborate in assessing and planning intervention programmes. This article analyses parental and professional assessments of children with ASD, in the dimensions of social communication, repetitive behaviours and restricted interests, and sensory processing. The study presents contrasting perspectives from professionals and parents from a range of socio-academic backgrounds. The sample consists of 136 Portuguese children (aged three to six years old) with ASD and involves children, parents and professionals from across the country. All children, at the time, were in preschool and receiving early special education intervention. Parents and professionals used the Assessment Scale for Children with ASD to complete the assessments. The results show that parents rate children’s development and learning more positively compared to professionals; and that this difference is more significant in the field of social communication. Further, parents with higher academic qualifications showed statistically significant differences in comparison with professionals in the social communication dimension. These findings are discussed in relation to the literature and some suggestions are made regarding certain practices related to intervention in early childhood.